Indian Consumers’ Materialistic Values: An Examination of Dimensionality and Instrument Development Through Exploratory Factor Analysis - Vohra, Aastha Verma (Indian Journal of Marketing, 2015)
In this research paper, I attempted to find out the dimensions /factors of materialistic values/ materialism of Indian consumers, which is a behavior demonstrated by the consumers world over to obtain worldly possessions. There is sufficient discourse present in extant literature about the materialistic tendency of Western consumers or the consumers from the developed parts of the world. However, the presence of this particular consumer behavioral trait is yet to be completely understood in the less affluent societies of the world, which are no longer isolated from the global marketing activities of the international marketers due to the forces of globalization. Today, the consumers of these developing markets have also become an attractive consumer segment to cater to by MNCs because of the factors like globalization of the market place, rising disposable incomes, and changing culture and lifestyle. In such a scenario, a potent research instrument to gauge the materialistic value of Indian consumers would be of great use for international markets, research scholars, and policy makers. The present research examined the dimensions of materialism through the use of content validity study, exploratory factor analysis, and reliability analysis of the adapted materialism scales of Belk (1985) and Richins and Dawson (1992).